Evaluation of green solution potentials of unripe banana (musasapientum) peel biomass - Leizou, Kaywood Elijah; Ashraf, Muhammad Aqeel; Abu Samah, Mohd Armi; Khan Chowdhury, Ahmed Jalal (ZIBELINE INTERNATIONAL PUBLISHING, 2019)
In the present study, the green solution potentials of unripe banana (musa sapientum) peel biomass were evaluated by using the adsorbent for the removal of Cd (II) and Cr (VI) from aqueous solution. The batch method was employed: parameters such as pH, initial concentration, adsorbent dose and contact time were studied. Unripe banana peel was found to remove Cd (II) and Cr (VI) ions from aqueous solutions. Removal rate of Cd (II) was found to increase from pH > 4, while Cr (VI) decreases from pH > 4. Langmuir and Freundlich models were applied to adsorption equilibrium data to find the best fit amongst these models. Langmuir model type 1, with R2 = 0.999 best fit for Cr (VI) adsorption data. The separation parameter, RL values were less than 1.0 i.e., 0.01219, 0.00613, 0.00308, and 0.00205 with corresponding initial concentrations of (50, 100, 200 and 300) mg/L respectively. This indicates that adsorption of Cr (VI) ion on unripe banana peel biomass was favourable to Langmuir isotherm, while Freundlich model with R2 = 0.949 best fit Cd (II) ion with (n) value of 1.1, which was favourable adsorption. Thus, the results of these findings showed that unripe banana peel biomass could be effectively and efficiently utilized for the removal of Cd (II) and Cr (VI) ions from aqueous solution.